Middle Proterozoic vein-hosted gold deposits in the Pontes e Lacerda region, southwestern Amazonian craton, Brazil - Geraldes, Mauro C.; Figueiredo, Bernardino R.; Tassinari, Colombo C. G.; Ebert, Hans D. [UNESP] (Taylor & Francis, 1997)
Structural, geochemical, and isotope studies were carried out on the gold deposits of the Pontes e Lacerda region (Mato Grosso state, Brazil), where rocks of the Aguapei and Rondoniano mobile belts (southwestern Amazonian craton) occur. The orebodies are hosted in metavolcanic, gneiss-granite, quartzite, tonalite, and granite units. Tectonics involve oblique overthrusting (from northeast to southwest), which led to the formation of recumbent folds and thrusts (pathways for the mineralizing fluids), upright folds, and faults with dominant strike-slip component. These unconformities represent potential sites for mineralization. During geological mapping, it was observed that the orebodies consist of quartz, pyrite, and gold, and that the hydrothermal alteration zone contains quartz, sericite, pyrite (altered to limonite), and magnetite (altered to hematite). Chalcopyrite, galena, and sphalerite occur only in the Onça deposit. Chemical analysis of sulfides indicates high contents of Bi, Se, and Te in sulfides and gold, suggesting plutonic involvement in the origin of hydrothermal solutions. K-Ar dating of hydrothermal sericites from gold veins yielded ages in the range from 960 to 840 Ma, which may indicate the age of original crystallization of sericite. Pb-Pb dating in galenas yielded model ages in the range from 1000 to 800 Ma for the Onça deposit, which is in agreement with K-Ar ages. Pb-isotopic ratios indicate high U/Pb and low Th/Pb for the upper-crustal Pb source before incorporation in galena crystals. The Pontes e Lacerda gold deposits yielded ages correlated to the Aguapei event and probably were formed during a Proterozoic contractional tectonic period in the southwestern part of the Amazon craton, which may characterize an important metallogenic epoch in the Pontes e Lacerda region.
Keywords: gold; mineralization; proterozoic; Brazil, Pontes e Lacerda